Амплификация генов дигидрофолатредуктазы и их перенос в животные клетки - Кузнецова, Н.Н.; Музамедханова, Ф.С.; Нуриджанянц, С.С.; Абдукаримов, А.А.; Садыков, А.С. (Биополимеры и клетка, 1987)
Описана новая сублиния клеток китайского хомячка BFFR³, выведенная на основе фибробластоподобной клеточной линии Blld-ii-FAF28 (клон 431), резистентная к 132 мкг/мл метотрексата. Хромосомный анализ резистентных клеток позволил обнаружить специфические изменения кариотипа в виде гомогенно окрашенных областей на 2-й и 5-й хромосомах, а также изменение модального класса резистентных клеток. Используя ДНК резистентных клеток, осуществлен перенос лекарственной устойчивости в чувствительные FStk–клетки. Описано нову сублінію клітин китайського хом’ячка BFFR³, виведену на основі фібробластоподібної клітинної лінії Blld-ii-FAF28 (клон 431), резистентну до 132 мкг/мл метотрексату. Хромосомний аналіз резистентних клітин дозволив виявити специфічні зміни каріотипу у вигляді гомогенно забарвлених областей на 2-й і 5-й хромосомах, а також зміну модального класу резистентних клітин. Використовуючи ДНК резистентних клітин, здійснено перенесення лікарської стійкості у чутливі FStk-клітини. A new subline of Chinese hamster cells BFFR³, derived from fibroblast-like cell line Blld-ii-FAF28 (431 clone), and resistant to 132 (μg/ml of metotrexate(mtx) has been described. Karyotype study has revealed the specific changes in resistant cells in the form of homogeneously stained within chromosomes 2 and 5, and at the same time single double minute chromosomes being amplified dihydrofolate reductase genes. Variation in the modal class of resistant cells is found in the process of selection, the cells with 24 chromosomes (40 %) being dominated. The transfer of drug resistance has been performed while treating mtx-sensitive FStk~ cells with DNA, isolated from resistant BFFB3 cells and the formation of colonies with low frequency (1.04-10~6) has been shown. Thus, the amplification of target-genes under action of mtx underlies variability of cell population.